Enhancing Energy Efficiency in Methanol-to-DME Conversion through Process Modification and Heat Integration - Salma Salsabila; Meirisa Ayu Saputri; Jorsch Pieter Benhard Sirait; Samuel Kurniawan; Sera Amelia; Alvin Ananta Putra (Journal of Chemical Engineering Research Progress, 2025)
Enhancing energy efficiency in dimethyl ether (DME) production is critical for reducing utility consumption and improving process sustainability. This study investigates the impact of targeted modifications to the methanol dehydration system on thermal performance and operational stability. The proposed configuration incorporates an expanded heat-integration network, additional feed-conditioning units, and a split-recycle arrangement to optimize energy recovery and maintain reactor stability. A water knock-out vessel and supplementary exchangers were also integrated to improve separation efficiency and reduce reboiler duty. Comparative process simulations were performed using with the NRTL thermodynamic model to evaluate the baseline and modified flowsheets. Results indicate that the optimized design achieves a 35.55% increase in energy efficiency while preserving the original methanol conversion level of 50.35%, confirming that reduced energy demand does not compromise reaction performance. These findings demonstrate that the proposed modifications provide a more energy-efficient and industrially viable configuration for DME production, offering a strong foundation for future optimization and process intensification strategies. Copyright © 2025 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).